Adolescent EFL learners’ English assessment preferences: Emergence of ICT-based evaluation - Pratama, Putu Yoga Sathya; Santosa, Made Hery (JEES (Journal of English Educators Society), 2023)
The incorporation of technology into education has impacted numerous facets, assessment being no exception. This study employed a descriptive-qualitative methodology to investigate the English assessment preferences of adolescent learners. There were 126 eighth-grade students voluntarily engaged and completed an open-ended online survey about issue under discussion. Through interactive data analysis, gathered data were examined qualitatively. The primary results portray three main findings: 1) in general, the majority of participants tend to prefer written over spoken form of assessment in the English lesson; 2) more participants prefer game quizzes as the assessment preference; and 3) the majority of participants believe English assessment should be differentiated to accommodate learners’ diversity. Presented findings illustrate a pattern indicating English proficiency of learners significantly influences their assessment preferences. Additionally, it is discovered that ICT-based evaluation has emerged among recent adolescent learners. As the results span a vast range of topics, it is anticipated that additional study will be conducted utilizing this research's gaps. HIGHLIGHTS: Generally, the majority of investigated adolescent learners tend to prefer written over spoken form of assessment in the English lesson. In specific, there are more investigated adolescent learners who prefer game quizzes as their assessment preference over the form of English assessments. The majority of investigated adolescent learners believe that English assessment should be differentiated to accommodate learners’ diversity.